Statistical mechanics of 'Unwanted Electroactuation' in nanoporous supercapacitors - Rochester,CC; Pruessner,G; Kornyshev,AA (Electrochimica Acta, 2015)
Nanoporous electrodes have the potential to increase the surface electrode interfacial area and the stored energy density of a supercapacitor. However, structural deformation of the electrode can become apparent when the size of the pore is comparable to the size of a charging ion. After many cycles this could cause wear and degradation. We present a theoretical study of this ‘Unwanted Electroactuation’ in a carbon electrode wetted with an ionic liquid. We incorporate changes of the carbon-carbon bond length due to electrochemical doping of the pore walls and steric effects related to counterion insertion into the pore via a modified Ising model of charge storage. When considering the total electrode deformation these effects either complement or compete with each other, depending on the polarisation of the electrode. Our model shows qualitative agreement with the features of the experimentally observed expansion caused by variation of electrode potential.